2009
DOI: 10.1016/j.neuroimage.2009.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of white matter degeneration in elderly subjects by magnetic resonance diffusion and FLAIR imaging correlation

Abstract: Fluid attenuated inversion recovery (FLAIR) and diffusion tensor imaging (DTI) techniques have been widely used to evaluate white matter (WM) alterations associated with aging, dementia and cerebral vascular disease. The relationship between FLAIR detected WM lesions (WML) and DTI detected WM integrity changes, however, remains unclear. To investigate this association, voxelwise correlations between 4 Tesla DTI and FLAIR images from elderly subjects were performed by relating WML volume and intensity in FLAIR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Two had extensive confluent deep white matter hyperintensities (WMH), and 5 had either small- or medium-sized focal WMH in deep white matter. WMH may affect white matter microstructural integrity (FA), though a relationship between these measures is only just beginning to be understood (Zhan et al, 2009). It is also possible that relationships between white matter tract integrity and specific cognitive tests were present, but not detected.…”
Section: Discussionmentioning
confidence: 99%
“…Two had extensive confluent deep white matter hyperintensities (WMH), and 5 had either small- or medium-sized focal WMH in deep white matter. WMH may affect white matter microstructural integrity (FA), though a relationship between these measures is only just beginning to be understood (Zhan et al, 2009). It is also possible that relationships between white matter tract integrity and specific cognitive tests were present, but not detected.…”
Section: Discussionmentioning
confidence: 99%
“…For those subjects with significant white matter lesion load, lesion areas, defined as regions with abnormal signal intensity typically 25 % greater than the average intensity of surrounding normal-appearing white matter (Zhan et al, 2009), were extracted from bias field corrected FLAIR images (FAST; FMRIB, Oxford, UK).…”
Section: Methodsmentioning
confidence: 99%
“…First, the number of studies that have measured both FLAIR and DTI in the same individuals, and directly evaluated what information about prevalent aging-related white matter pathology is shared between the two or unique to one or the other, is still very small. One study has suggested that by investigating relationships between FLAIR signal intensity and DTI measures within WMHs, we can effectively categorize WMHs according to the severity of WMH dysfunction, but the clinical value of such deeper characterization of WMH severity is currently unclear (Zhan et al 2009). Second, while several serial FLAIR studies have used multiple scans per individual to directly chart the longitudinal course of WMH changes in relation to risk factors and cognition, only three analogous serial DTI studies have appeared that report associations between DTI-based measures and ancillary variables of interest (Charlton et al 2010;Teipel et al 2010;Sullivan et al 2010).…”
Section: Relation To Flairmentioning
confidence: 99%